Analisis Faktor-Faktor yang Memengaruhi Tingkat Perolehan Margin dengan Akad Murabahah pada Bank Syariah X - Muhammad Yusuf; Rini Kurnia Sari (Binus Business Review, 2013)
This study aims to find out and analyze the factors that affect the level of turnover margin financing murabahah contract on Sharia Bank X and to know the most influential factor on the level of revenue and margins with murabaha contract to know the calculation of turnover margin murabaha financing. The population of this research was the financial statement and the sample was quarterly income statement from 2005 until 2011. This study employed a secondary data collection methods and field research by doing research on Muamalat Institute. Analysis tools used SPSS software version 19.0. Based on the results, the study indicated that factors affecting the level of margin financing murabaha are the overhead cost factor with R2 of 0.73 and test results of F-test of 72.684, as well as a significant level of 0.0001 and administrative costs with the R2 of 0.93 and test results F-test of 72.684, as well as a significant level of 0.037. While, the financing volume factor does not affect the rate of margin on murabaha financing. The most influential factor is the overhead factor.